2015
DOI: 10.1016/j.neubiorev.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Making the case for mobile cognition: EEG and sports performance

Abstract: In the high stakes world of International sport even the smallest change in performance can make the difference between success and failure, leading sports professionals to become increasingly interested in the potential benefits of neuroimaging. Here we describe evidence from EEG studies that either identify neural signals associated with expertise in sport, or employ neurofeedback to improve performance. Evidence for the validity of neurofeedback as a technique for enhancing sports performance remains limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 100 publications
(103 reference statements)
1
113
1
7
Order By: Relevance
“…Indeed, a great deal of research demonstrated an association between particular electroencephalographic patterns and performance in specific cognitive tasks and activities. For this reason, electroencephalography is used as a high-resolution temporal technique to understand performance and its improvements in the context of sports sciences 17 .…”
Section: Psychophysiological Monitoring: a Multidimensional And Multimentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a great deal of research demonstrated an association between particular electroencephalographic patterns and performance in specific cognitive tasks and activities. For this reason, electroencephalography is used as a high-resolution temporal technique to understand performance and its improvements in the context of sports sciences 17 .…”
Section: Psychophysiological Monitoring: a Multidimensional And Multimentioning
confidence: 99%
“…This rhythm was also studied as a marker of resources allocation during motor programming 32 . Beta oscillation (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30),on the other hand, has a central position in the treatment of sensorimotor information and serves as a functional link between different brain regions such as the pre-motor, motor (M1), and somatosensory (S1) cortex, the supplementary motor area, and the cerebellum 31 . Beta oscillation could play the role of a motor "binding" linking the different commands related to a global gesture as suggested for sensory awareness 30 .…”
Section: Electroencephalography and Cortical Activity In Sportmentioning
confidence: 99%
“…The research to less unobtrusive EEG solutions for mobile cognition is making rapid progress. Miniaturized EEG electrodes integrated in discreet baseball caps and individualized ear pieces have recently been reported [13,14]. It remains an open question which type of cognition can be captured accurately enough with these devices, as the electrodes only cover a limited region of the scalp.…”
Section: Prototype Evaluationmentioning
confidence: 99%
“…The psychological state of the individual, when properly measured neurocognitively, will identify characteristics and patterns of brain activity and allow for objective classification improving clinical outcomes [24,25]. Neurocognition refers to correlating emotional / psychological factors and cognitive processing with physiological patterns of neural activity [25].…”
Section: Future Directions: Neurocognitive Assessmentmentioning
confidence: 99%
“…Thus, neurofeedback provides an individual with the ability to manipulate their own brain activity toward a specific goal. A recent study utilized neurofeedback as a means for improving sport performance [24]. Thus, as a result of one learning to control their own brain patterns, this modality could provide improvement for individuals to RTS caused by neurocognitive deficits.…”
Section: Future Directions: Neurocognitive Assessmentmentioning
confidence: 99%